Funding strategies for business development: sustainability and growth - Alias, Aidi Azhar; Roslin, Hanis Amirah; Ali, Jurainah; Abdullah, Nur Hidayah; T.K. Muthu Koya Thangal, Thahira Bibi; Mohd Zabidi, Mahfuzah (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
This study analyses incubator business development program held by HayRadiance Foundation through its viable activities. By engaged partnerships, unified technology, and focused on sustainability, the foundation is not only created economic opportunities but also contributed to the wider goal of global interconnectedness. Through this case study, the author discussed how targeted strategies can empower entrepreneurs and communities in a rapidly evolving global landscape